O narrador-personagem: instabilidade romanesca e subjetividade fílmica entre O Matador e O homem do ano - Teles, Maria de Lourdes (2008)
This is an analysis of O Matador (The Killer), a novel by Patrícia Melo, and its transposition to the film (2002) O homem do ano (The man of the year) by the film maker José Henrique Fonseca, pointing at the deviations in the narrative focalization and its effects after the book adaptation. The leading thread is the narrator s role in the construction of the fable both in the novel and the film. Even presenting himself as an autodiegetic narrator, Máiquel decentralizes, in the novel, his role as the central subject of the narrative whenever he clearly evinces his absence putting himself, at the same time, in the condition of reader and listener of the story he himself narrates. In the film, on the contrary, Máiquel reports, in off, his trajectory in the world of crime. In his report the events are narrated linearly. To explain this linearity of the filmic text, it was considered the hypothesis of the establishment of a narrator with an angle of vision fixed in the facts, obtained by means of a camera, that is, in the film, image and voice express Máiquel s thoughts, feelings, and perceptions. Thus, this narrator cannot hide his presence nor change his point of view, as the narrator in the novel does. Starting from these perspectives, an attempt was made to analyze both texts by using the theoretical concepts of Friedman (1967), Bourneuf (1976) e Genette (1989), in order to evaluate the role of the subject of enunciation in the narrative plot of the novel and film. The filmic transmutation was analyzed in the light of the theories of Benjamin (1983), Campos (1992), Einsenstein (2002) e Pudovkin (2003), with the purpose of tackling aspects which explain the subjectivity of the film narrative and how it took shape, since the film was here considered as a re-creation of the novel